Comparative Effects of Ketamine Versus Magnesium Sulfate on Pain Management after Spine Surgery: A Double-Blind Randomized Clinical Trial - Seyedbabak Mojaveraghili; Mohammadali Izadfar; Naser Behnampour (Archives of Anesthesia and Critical Care, 2026)
Background: Spinal fusion surgery, as one of the treatment options for back pain, often results in significant postoperative pain due to complexity and multiple incisions. Glutamate receptors such as NMDA are among the main receptors involved in this process, causing central hyperalgesia and sensitization and ultimately accelerating pain processing in the CNS. Therefore, NMDA receptor antagonists such as ketamine and magnesium sulfate can be considered as suitable options for treating pain caused by these surgeries. A prospective study was conducted to compare the effects of ketamine and magnesium sulfate on pain control in these patients. This double-blind clinical trial was performed on 72 patients undergoing fusion surgery, referred to the 5th Azar Medical & Educational Center of Gorgan in 2020-2022. Methods: In group A, 50mg/kg of magnesium sulfate along with CVE=5 ml/kg was infused over 20 minutes, and then 500 mg/h of magnesium sulfate was given during and up to 48 hours after surgery. In group B, 0.5 mg/kg of ketamine was given as a bolus after patient positioning and 2 minutes before surgical incision, followed by 2.5 mcg/kg/h of ketamine during and up to 48 hours after surgery. Pain was evaluated using the NRS scale from admission to recovery up to 48 hours after surgery, and the amount of opioid consumption was recorded. Results: Both ketamine and magnesium sulfate led to a significant reduction in pain during the first 48 hours after surgery (P value